Respuesta :
Answer:
me memory is coming back a little
Step-by-step explanation:
Simplifying
3x + 5 = 9x + -17
Reorder the terms:
5 + 3x = 9x + -17
Reorder the terms:
5 + 3x = -17 + 9x
Solving
5 + 3x = -17 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
5 + 3x + -9x = -17 + 9x + -9x
Combine like terms: 3x + -9x = -6x
5 + -6x = -17 + 9x + -9x
Combine like terms: 9x + -9x = 0
5 + -6x = -17 + 0
5 + -6x = -17
Add '-5' to each side of the equation.
5 + -5 + -6x = -17 + -5
Combine like terms: 5 + -5 = 0
0 + -6x = -17 + -5
-6x = -17 + -5
Combine like terms: -17 + -5 = -22
-6x = -22
Divide each side by '-6'.
x = 3.666666667
Simplifying
x = 3.666666667
The value of variable x in the expression is 3.666666667.
What is the value of x in an expression?
The algebraic expression should be any one of the forms such as addition, subtraction, multiplication, and division. To find the value of x, bring the variable to the left side and bring all the remaining values to the right side. Simplify the values to find the result.
Given expression is
3x + 5 = 9x + -17
Reordering the terms:
5 + 3x = 9x + -17
Reorder the terms again:
5 + 3x = -17 + 9x
Solving
5 + 3x = -17 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, and all other terms to the right.
Add '-9x' to each side of the equation.
5 + 3x + -9x = -17 + 9x + -9x
Combine like terms: 3x + -9x = -6x
5 + -6x = -17 + 9x + -9x
Combine like terms: 9x + -9x = 0
5 + -6x = -17 + 0
5 + -6x = -17
Add '-5' to each side of the equation.
5 + -5 + -6x = -17 + -5
Combine like terms: 5 + -5 = 0
0 + -6x = -17 + -5
-6x = -17 + -5
Combine like terms: -17 + -5 = -22
-6x = -22
Divide each side by '-6'.
x = 3.666666667.
Learn more about the value of the variable on:
https://brainly.com/question/4009675
#SPJ2